Róża Wojciecha Smarzowskiego – portret miłości kulturowo zakorzenionej - Szpulak, Andrzej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Róża by Wojciech Smarzowski: Portrait of a Culturally Rooted Love The article presents an interpretation of the love story in Wojciech Smarzowski’s film Róża (2011) in the context of references to culture deeply rooted in the European tradition of representing this theme. It indicates the melodramatic elements presented in this film, as well as the leading role of the myth of romantic love in creating this thread. Clearly visible is a male perspective view of reality in Smarzowski’s film.